1985
DOI: 10.1139/y85-230
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pituitary responses to synthetic ovine corticotrophin releasing factor in fetal sheep

Abstract: The rise in cortisol in fetal sheep during late pregnancy has been related to increased responsiveness of the adrenal to ACTH. Most reports have suggested that plasma ACTH concentrations rise coincident with or after the prepartum increase in cortisol. To reexamine the relationship of cortisol with basal immunoreactive ACTH (IR-ACTH) throughout the last 40 days of pregnancy and to determine changes in fetal pituitary responsiveness during this time, we measured basal and synthetic ovine corticotrophin-releasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
1
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 21 publications
7
53
1
1
Order By: Relevance
“…It has been reported that fetal ACTH plasma levels increase progressively between 110 and 140 d gestation, whereas fetal cortisol levels remain low between 110 -120 d and increase between 125-140 d gestation (32). McMillen et al (33) also found that fetal plasma ACTH concentrations double between 120 and 136 d and 140 and 143 d gestation.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that fetal ACTH plasma levels increase progressively between 110 and 140 d gestation, whereas fetal cortisol levels remain low between 110 -120 d and increase between 125-140 d gestation (32). McMillen et al (33) also found that fetal plasma ACTH concentrations double between 120 and 136 d and 140 and 143 d gestation.…”
Section: Discussionmentioning
confidence: 96%
“…adrenocorticotropic hormone; ovine fetus IN HUMANS AND MANY MAMMALIAN SPECIES, the late-gestation surge in fetal plasma cortisol levels stimulates final stage development of the lung and other organ systems (7,22) and indeed, in sheep, initiates birth (19,32). Parturition occurring before this surge is associated with increased fetal mortality and morbidity, most notably as a consequence of lung immaturity.…”
mentioning
confidence: 99%
“…Another explanation may be that factors other than ACTH stimulate the adrenal gland a t this stage of gestation. For instance, a-melanocyte-stimulating hormone, growth hormone and proopiomelanocortin-derived peptides have all been shown to have stimulatory actions on the adrenal gland although their precise role in the physiologic control of adrenocortical activity is not understood (20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%